Strategies for teaching vocabulary at Combatientes de Tapi high school - Cabezas-LLerena, Kerly Yesennia; Barriga-Fray, Luís Fernando; Barriga-Fray, Johanna Isabel; Flores-Galeano, Jennifer Karina (Dominio de las Ciencias, 2019)
The present study describes how English language teachers apply strategies for teaching vocabulary. It was performed with Primer año de bachillerato students, class D at Combatientes de Tapi high school from January to May 2019. The purpose of this work is to explore the use of vocabulary teaching strategies. The type of this study is qualitative of exploratory level. The research was carried out with a population of thirty-five students. The qualitative method employed was the ethnographic. A non-participatory observation technique was used since the researcher plays a passive role; the data collection instrument was a ckeck-list designed by the researcher. After the analysis of the data, it was obtained that teachers usually apply four teaching vocabulary strategies that adjust to the needs of the students.